The development of Religious Education in Secondary Schools in Zimbabwe in response to Pluralism - Muhamba, Shepherd (Department of Religious Studies, 2021)
This study has explored and described how Religious Education (RE) in Secondary Schools in Zimbabwe has developed in response to pluralism. It has been inspired by my teaching experience in different secondary schools in the country. There has been a growing need in Zimbabwe to expand the horizon for RE as the nation is becoming more sensitive to religious diversity among the learners. The government through its Ministry of Primary and Secondary Education has been implementing changes in RE secondary schools with the hope of making it open to pluralism. This study shows that despite the government's efforts, little has changed in the teaching of RE in the classroom. This has been a result of failure by the government to engage teachers in the implementation of the proposed changes. There is a strong relationship between teachers and religious education in schools. They are the main determinant of the quality of education learners receive as they make choices, both conscious and unconscious, in regard to how to structure academic and social relationships in the classroom. Their perceptions towards religious pluralism also influences the way they teach about religion in the classroom. Unfortunately, this relationship between teachers and religious education was not given much attention in the development of the subject in secondary schools in Zimbabwe. This study investigates this relationship and contributes some knowledge in this area for further discussion.